Regional Differentiation of the Innovative Potential of Enterprises in the Czech Republic - Hlaváček, Petr; Mata, Martin (Regionalne zróżnicowanie potencjału innowacyjnego przedsiębiorstw w Czechach, 2022)
This article presents the results of a survey of innovative activities of enterprises in the Czech Republic and a comparison of differences between regions. The goal is to analyse the approach of companies, examine how they evaluate their innovation activities and the implementation of R&D, and find out if there are inter-regional differences in the innovation activities of companies in chosen categories. The data were collected via a questionnaire survey of companies across regions in coordination with the Technology Agency of the Czech Republic. The research revealed that more enterprises were in a dependent position, providing partial functions within the concern, or as suppliers in their respective production chains. At the same time, companies are actively preparing for the constantly changing production and economic environment and some also have ambitions to become pioneers of innovative change. Even at regional level, some differences were found, given the different stage of development and competitiveness of the regions. Through the priorities of regional innovation strategies, public support should prepare suitable conditions for the development of new industrial and tertiary sectors in the region.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 1-12
Keywords: innovation potential; region; Czechia; potencjał innowacyjny; Czechy